Examining protein–protein interactions using endogenously tagged yeast arrays: The Cross-and-Capture system - Suter, Bernhard; Fetchko, Michael J.; Imhof, Ralph; Graham, Christopher I.; Stoffel-Studer, Ingrid; Zbinden, Caroline; Raghavan, Maanasa; Lopez, Lianet; Beneti, Lucija; Hort, Jacqueline; Fillingham, Jeffrey; Greenblatt, Jack F.; et al. (Genome Research, 2007)
Comprehensive approaches to detect protein–protein interactions (PPIs) have been most successful in the yeast model system. Here we present “Cross-and-Capture,” a novel assay for rapid, sensitive assessment of PPIs via pulldown of differently tagged yeast strain arrays. About 500 yeast genes that function in DNA replication, repair, and recombination and nuclear proteins of unknown function were chromosomally tagged with six histidine residues or triple VSV epitopes. We demonstrate that the assay can interrogate a wide range of previously known protein complexes with increased resolution and sensitivity. Furthermore, we use “Cross-and-Capture” to identify two novel protein complexes: Rtt101p–Mms1p and Sae2p–Mre11p. The Rtt101p–Mms1p interaction was subsequently characterized by genetic and functional analyses. Our studies establish the “Cross-and-Capture” assay as a novel, versatile tool that provides a valuable complement for the next generation of yeast proteomic studies.
10.1101/gr.6667007